2022
DOI: 10.21468/scipostphys.12.3.085
|View full text |Cite
|
Sign up to set email alerts
|

Enstrophy from symmetry

Abstract: We study symmetry principles associated with the approximately conserved enstrophy current, responsible for the inverse energy cascade in non relativistic 2+1 dimensional turbulence. We do so by identifying the accidental symmetry associated with enstrophy current conservation in a recently realized effective action principle for hydrodynamics. Our analysis deals with both relativistic and non relativistic effective actions and their associated symmetries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These currents can be further generalized in the presence of additional conserved U (1) charges, or if the flow is barotropic. See, e.g., [5]. For α = 1 and q = 1 we obtain (1.1).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…These currents can be further generalized in the presence of additional conserved U (1) charges, or if the flow is barotropic. See, e.g., [5]. For α = 1 and q = 1 we obtain (1.1).…”
mentioning
confidence: 79%
“…Its existence is crucial for the appearance of the inverse energy cascade in two dimensional turbulence [1] and its dynamics is used in modeling turbulent dependent phenomena. While enstrophy is well understood in the context of incompressible fluid flow, barotropic flow and relativistic fluids (see [2][3][4][5]), little is known regarding its existence for more general flows with varying degrees of symmetry. The goal of this work is to study enstrophy conservation for generic fluids in two spatial dimensions with little symmetry.…”
mentioning
confidence: 99%
“…It may well be that relativistic turbulent flow is not universal [17]. A study of the relativistic entropy current can be found in [8,26,27].…”
Section: The Boundary Stress Tensormentioning
confidence: 99%
“…These currents can be further generalized in the presence of additional conserved U(1) charges, or if the flow is barotropic. See, e.g., [5]. For α = 1 and q = 1 we obtain (1).…”
Section: Introductionmentioning
confidence: 98%
“…Its existence is crucial for the appearance of the inverse energy cascade in two dimensional turbulence [1] and its dynamics is used in modeling turbulent dependent phenomena. While enstrophy is well understood in the context of incompressible fluid flow, barotropic flow and relativistic fluids (see [2][3][4][5]), little is known regarding its existence for more general flows with varying degrees of symmetry.…”
Section: Introductionmentioning
confidence: 99%